(untitled) (Nigerian Journal of Technology, 2015)
Under normal Fluid Catalytic Cracking (FCC) conditions, coke is the most important factor that affects catalyst activity. A pseudo homogeneous two - dimensional (2D) model of an industrial FCC riser is here presented. The FCC riser models of previous researchers were mostly based on the assumption of negligible mass transfer resistance and 1D plug flow. These assumptions undermine the accuracy of the models by over-predicting the riser residence time while under-predicting the reaction time. Mass transfer resistance was incorporated in the reactor model to enhance the accuracy of the results. Finite difference was used to discretise the model equation. This investigation has advanced research into the modeling of FCC riser by predicting catalyst coke content as a function of reaction temperature. The yields of LCO, gasoline, gas and coke that were predicted by the model for industrial risers were 15.54wt%, 49.70wt%, 18.01wt% and 4.90wt% respectively. A feed stock (VGO) conversion of 79.28% was predicted by the model. An optimal operating temperature range of 786K<T<788K was predicted for the riser. http://dx.doi.org/10.4314/njt.v34i2.14